Quantitative analysis of Bordeaux red wine precipitates by solid-state NMR: Role of tartrates and polyphenols. (15th May 2016) - Prakash, Shipra; Iturmendi, Nerea; Grelard, Axelle; Moine, Virginie; Dufourc, Erick
Highlights: A method to produce precipitates in red wines for analytical purposes was established. Amount of precipitate depends on temperature, vintage, grape variety & wine stability. Solid state 13 C-CPMAS NMR spectroscopy allows identifying molecular components in intact wine precipitates. Precipitates are dominated by potassium bitartrate, tannins, & polysaccharides. Abstract: Stability of wines is of great importance in oenology matters. Quantitative estimation of dark red precipitates formed in Merlot and Cabernet Sauvignon wine from Bordeaux region for vintages 2012 and 2013 was performed during the oak barrel ageing process. Precipitates were obtained by placing wine at −4 °C or 4 °C for 2–6 days and monitored by periodic sampling during a one-year period. Spectroscopic identification of the main families of components present in the precipitate powder was performed with 13 C solid-state CPMAS NMR and 1D and 2D solution NMR of partially water re-solubilized precipitates. The study revealed that the amount of precipitate obtained is dependent on vintage, temperature and grape variety. Major components identified include potassium bitartrate, polyphenols, polysaccharides, organic acids and free amino acids. No evidence was found for the presence of proteins. The influence of main compounds found in the precipitates is discussed in relation to wine stability.